2008
DOI: 10.1007/s00726-008-0133-7
|View full text |Cite
|
Sign up to set email alerts
|

FXIIIA and TGF-β over-expression produces normal musculo-skeletal phenotype in TG2-/- mice

Abstract: Transglutaminase (TGs) enzymes and proteins crosslinking have for long time been implicated in the formation of hard tissue development, matrix maturation and mineralization. Among the TGs family members, in the context of connective tissue formation, TG2 and Factor XIII are expressed in cartilage by hypertrophic chondrocytes. Here, we analyse the morphological consequences of TG2 deficiency, during the development of skeletal elements. When TG2 is absent, there are not gross abnormalities in the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 33 publications
(39 reference statements)
0
18
0
Order By: Relevance
“…A plausible explanation for the discrepancy between the in vitro and in vivo studies accounts for functional redundancy between TGs due to high similarity in their substrate specificity (Achyuthan et al , 1996), and as a result, functional compensation for loss of each isoform by other TGs in embryonic development. Thus, compensatory activation of FXIIIa in the TG2 −/− cells supports total TG activity and the pattern of protein cross-linking identical in TG2 −/− and wild type cartilage (Nurminskaya and Kaartinen, 2006) (Nurminskaya et al , 2006; Tarantino et al , 2008). In addition, TG5, TG1 and TG7 have been postulated to compensate for the loss of TG2 in various tissues (Grenard et al , 2001; Johnson et al , 2008).…”
Section: Introductionmentioning
confidence: 65%
“…A plausible explanation for the discrepancy between the in vitro and in vivo studies accounts for functional redundancy between TGs due to high similarity in their substrate specificity (Achyuthan et al , 1996), and as a result, functional compensation for loss of each isoform by other TGs in embryonic development. Thus, compensatory activation of FXIIIa in the TG2 −/− cells supports total TG activity and the pattern of protein cross-linking identical in TG2 −/− and wild type cartilage (Nurminskaya and Kaartinen, 2006) (Nurminskaya et al , 2006; Tarantino et al , 2008). In addition, TG5, TG1 and TG7 have been postulated to compensate for the loss of TG2 in various tissues (Grenard et al , 2001; Johnson et al , 2008).…”
Section: Introductionmentioning
confidence: 65%
“…Both lines do, however, display impaired wound healing [34][35][36]. The relatively mild phenotypes of uninjured mice have previously been explained by invoking an overlap between the functions of FXIII-A and TG2 [11,12], although the predominant role bone deposition has been ascribed to FXIII-A [15].…”
Section: Discussionmentioning
confidence: 99%
“…Naturally occurring mutations in the human FXIII-A gene [9], and targeted knockouts in mice [10], are associated with a bleeding phenotype but not skeletal abnormalities. To reconcile this observation with the suggestion that FXIII-A has a role in bone deposition, it has been suggested that the homologous enzyme, transglutaminase 2, shows functional redundancy with FXIII-A [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…52 Therefore, OPN and BSP oligomerization in bone could be jointly orchestrated by the two enzymes; TG2 on the cell surface and FXIIIA in the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%